Chronic Intermittent Hypobaric Hypoxia Decreases High Blood Pressure by Stabilizing the Vascular Renin-Angiotensin System in Spontaneously Hypertensive Rats - Chen, Hua; Yu, Bin; Guo, Xinqi; Hua, Hong; Cui, Fang; Guan, Yue; Tian, Yanming; Zhang, Xiangjian; Zhang, Yi; Ma, Huijie (Frontiers in Physiology, 2021)
Background and Aims: Previous studies have demonstrated the anti-hypertensive effect of chronic intermittent hypobaric hypoxia (CIHH) in hypertensive rats. The present study investigated the anti-hypertensive effect of CIHH in spontaneously hypertensive rats (SHR) and the role of the renin-angiotensin system (RAS) in anti-hypertensive effect of CIHH. Methods: Fifteen-week-old male SHR and WKY rats were divided into four groups: the SHR without CIHH treatment (SHR-CON), the SHR with CIHH treatment (SHR-CIHH), the WKY without CIHH treatment (WKY-CON), and the WKY with CIHH treatment (WKY-CIHH) groups. The SHR-CIHH and WKY-CIHH rats underwent 35-days of hypobaric hypoxia simulating an altitude of 4000-m, 5 h per day. Arterial blood pressure and heart rate were recorded by biotelemetry, and angiotensin (Ang) II, Ang1–7, interleukin (IL)-6, tumor necrosis factor-alpha (TNF)-α，and IL-10 in serum and the mesenteric arteries were measured by enzyme-linked immunosorbent assay (ELISA) and immunohistochemistry, respectively. The microvessel tension recording technique was used to determine the contraction and relaxation of the mesenteric arteries. Hematoxylin and eosin and Masson’s staining were used to observe vascular morphology and fibrosis. Western blot was employed to detect the expression of the angiotensin-converting enzyme (ACE), ACE2, AT1, and Mas proteins in the mesenteric artery. Results: The biotelemetry result showed that CIHH decreased arterial blood pressure in SHR for 3–4 weeks (P<0.01). The ELISA and immunohistochemistry results showed that CIHH decreased Ang II, but increased Ang1–7 in serum and the mesenteries of SHR. In the CIHH-treated SHR, IL-6 and TNF-α decreased in serum and the mesenteric arteries, and IL-10 increased in serum (P < 0.05–0.01). The microvessel tension results revealed that CIHH inhibited vascular contraction with decreased Ang1–7 in the mesenteric arteries of SHR (P<0.05-0.01). The staining results revealed that CIHH significantly improved vascular remodeling and fibrosis in SHR. The western blot results demonstrated that CIHH upregulated expression of the ACE2 and Mas proteins, and downregulated expression of the ACE and AT1 proteins (P<0.05–0.01). Conclusion: CIHH decreased high blood pressure in SHR, possibly by inhibiting RAS activity, downregulating the ACE-Ang II-AT1 axis and upregulating the ACE2-(Ang1-7)-Mas axis, which resulted in antagonized vascular remodeling and fibrosis, reduced inflammation, and enhanced vascular relaxation.